Overview of underpinnings of tourism impacts: the case of Lisbon destination - Loureiro, S. M. C.; Ferreira, E.S.; Rosário, J.F. (The Routledge handbook of tourism impacts: Theoretical and applied perspectives, 2019)
Positive and negative tourism impacts have been a concern for both academics and destinations’ management. The current chapter intends (1) to provide an overview of underpinnings of tourism impacts and (2) to present the case of Lisbon destination. Tourism in Lisbon has grown in the last decade, and it has become one of the first capital cities in Europe in terms of visitors. In this vein, we describe this evolution and give a characterization of Lisbon as a destination. Finally, the chapter provides managerial recommendations and suggestions for further research.